A Comparative Study of Smart Spectrophotometric Methods and a Densitometric Method for Simultaneous Determination of Binary Mixture of Canagliflozin and Metformin Hydrochloride. Issue 1 (2nd January 2018) - Elshahed, Mona S.; Mohamed, Dalia; Nasr, Tamer; Aboutaleb, Nageh; Zakaria, Ola
Abstract: Simple and sensitive Spectrophotometric methods and a densitometric thin layer chromatographic method (TLC) are developed and validated for simultaneous determination of binary mixture of metformin hydrochloride (MET) and canagliflozin (CFZ) in combined dosage form. Three spectrophotometric methods manipulating ratio spectra namely ratio subtraction, ratio difference and derivative ratio are used for the determination of MET in the presence of CFZ without preliminary separation, while CFZ is directly determined by measuring its absorbance at λmax 290 nm. The calibration curves follow Beer's law in the concentration range of 1 - 20 and 1 - 30 μg/mL for MET and CFZ respectively. A simple TLC method is developed where separation is performed on TLC silica gel plates 60F254 using toluene: Methylene chloride: methanol: water: glacial acetic acid in the volume ratio (20:15:15:1:0.25) as a mobile phase. Rf values are 0.55 ± 0.05 for CFZ and 0.21 ± 0.03 for MET, the linearity ranges are 0.3-4.5 and 0.5-5.5 μg/band for CFZ and MET respectively. The developed methods are successfully applied for the simultaneous determination of MET and CFZ in bulk and pharmaceutical formulation.